1985
DOI: 10.1002/1520-6629(198501)13:1<20::aid-jcop2290130104>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

The limits of fit: Examining the implications of person-environment congruence within different religious settings

Abstract: In this study, it was proposed that the implications of individual‐systems fit vary across different settings and across indicators of personal functioning internal and external to the setting. These predictions were put to test with 144 members of four churches differing in their perceived openness to different points of view and change. It was assumed that members with greater tolerance for ambiguity fit better within more autonomous open churches (MAOC), while members with less tolerance for ambiguity fit b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…However, this result should not be construed to indicate that perfect fit is always desirable. As Nielsen and Moos (1978) and Pargament et al (1985) noted, fitting in with one's environment can be a two-edged sword. What may lead to comfort (i.e., lack of distress) may not enhance growth and development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this result should not be construed to indicate that perfect fit is always desirable. As Nielsen and Moos (1978) and Pargament et al (1985) noted, fitting in with one's environment can be a two-edged sword. What may lead to comfort (i.e., lack of distress) may not enhance growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Doing this would increase the probability of finding no support for the person-environment fit hypothesis. Indeed, a nicely done study by Pargament, Johnson, Echemendia, and Silverman (1985) found only moderate support for the P-E fit hypothesis based on one variable, and they concluded that their results indicated that "limits of fit." It could also be concluded that the results were due to only a partial sampling of relevant fit variables.…”
Section: Person-environment Fitmentioning
confidence: 99%
“…Furthermore, the sample size did not allow an extension of the analyses, for example, through cross‐validation as suggested by Tinsley (2000) or by studying the interaction between the two dimensions of autonomy and relatedness. It also did not permit a comparison of individuals from the three different NRMs, which would have been interesting in the light of Pargament et al's (1985) finding that the significance of fit varied across different types of churches. Assuming that different churches attract correspondingly different kinds of people, this finding is in line with Edwards and Rothbard's (1999) report that the effects of fit vary according to level of needs and supplies.…”
Section: Discussionmentioning
confidence: 99%
“…The only application of P–E fit theory in the context of religion has been undertaken by Pargament and colleagues (Pargament, Johnson, Echemendia, & Silverman, 1985; Pargament, Tyler, & Steele, 1979), who studied the relationship between the fit of Jewish, Protestant, and Catholic church/synagogue members with their congregations and individual adaptation. In one study, they found that members with a high degree of fit with their church or synagogue differed from members with low fit in terms of their psychosocial competences; but none of the two groups displayed uniformly greater effectiveness across all competence scales that were applied (Pargament et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation